RELIGIOUS VALUES OF THE SONG “MARS PUSAT MA’HAD AL-JAMI’AH”: RIFFATERRE’S SEMIOTIC ANALYSIS - Rosyidah, Inayatur; Gufron, Gufron; Jumriyah, Jumriyah; Fatimah, Siti (Universitas Muhammadiyah Makassar, 2025)
The Mars Pusat Ma’had al-Jâmi’ah song is a symbolic representation of the institutional identity of the Pusat Ma’had al-Jâmi’ah at the State Islamic University of Maulana Malik Ibrahim Malang. This song not only expresses institutional spirit but also illustrates a harmonious integration of Javanese cultural elements and Islamic religious values. This study aims to explore the religious values embedded in the song’s lyrics and uncover their implicit meanings using Riffaterre’s semiotic theory. The research employed a qualitative descriptive method with data collected through intensive reading and textual annotation. Analysis followed the Miles, Huberman, and Saldana model, involving data collection, condensation, display, and conclusion drawing. The results reveal that the song serves not only as an aesthetic expression but also as an ideological and educational medium. The matrix or underlying meaning lies in the Ma’had’s mission to nurture a Qur’anic generation. This is reflected through two dominant models: the development of Qur’anic character and the reinforcement of Islamic symbols (syi’ar Islam) in social contexts. Key religious values identified include unwavering faith, personal and social piety, and sincere devotion to Islamic teachings reflected in real-life actions. Additionally, the song acts as a medium for internalizing spiritual values and affirming the cultural and religious identity of pesantren-based education. The findings imply that institutional mars songs hold potential as effective instruments for character development and the transmission of Islamic values, particularly in strengthening the cultural-spiritual identity within Islamic educational institutions.